Altered intrinsic excitability of hippocampal CA1 pyramidal neurons in aged PDAPP mice - Tamagnini, Francesco; Novelia, Janet; Kerrigan, Talitha L.; Brown, Jon T.; Tsaneva-Atanasova, Krasimira; Randall, Andrew D. (Frontiers in Cellular Neuroscience, 2015)
Amyloidopathy involves the accumulation of insoluble amyloid β (Aβ) species in the brain’s parenchyma and is a key histopathological hallmark of Alzheimer’s disease (AD). Work on transgenic mice that overexpress A suggests that elevated A levels in the brain are associated with aberrant epileptiform activity and increased intrinsic excitability of CA1 hippocampal neurons. In this study we examined if similar changes could be observed in hippocampal CA1 pyramidal neurons from aged PDAPP mice (20-23 month old, Indiana mutation: V717F on APP gene) compared to their age-matched WT littermate controls. Whole-cell current clamp recordings revealed that sub-threshold intrinsic properties, such as input resistance, resting membrane potential and hyperpolarization activated “sag” were unaffected, but capacitance was significantly decreased in the transgenic animals. No differences between genotypes were observed in the overall number of action potentials (AP) elicited by 500 ms supra-threshold current stimuli. PDAPP neurons, however, exhibited higher instantaneous firing frequencies after accommodation in response to high intensity current injections. The AP waveform was narrower and shorter in amplitude in PDAPP mice: these changes, according to our in silico model of a CA1/3 pyramidal neuron, depended on the respective reduction and increase of Na+ and K+ voltage-gated channels maximal conductances. Finally, the after-hyperpolarization (AHP), seen after the first AP evoked by a +300 pA current injection and after 50 Hz AP bursts, was more pronounced in PDAPP mice. These data show that Aβ-overexpression in aged mice altered the capacitance, the neuronal firing and the AP waveform of CA1 pyramidal neurons. Some of these findings are consistent with previous work on younger PDAPP, they also show important differences that can be potentially ascribed to the interaction between amyloidopathy and ageing. Such a change of IE properties over time underlies that the increased incidence of seizure observed in AD patients might rely on different mechanistic pathways during progression of the disease.